2018
DOI: 10.7287/peerj.preprints.26692v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet breadth and exploitation of exotic plants shift the core microbiome of tropical herbivorous beetles

Abstract: The beetle genus Cephaloleia has evolved in association with tropical ginger plants and for many species their specific host plant associations are known. Here we show that the core microbiome of six closely-related Costa Rican Cephaloleia species comprises only 8 bacterial groups, including members of the Acinetobacter, Enterobacteriacea, Pseudomonas, Lactococcus, and Comamonas. The Acinetobacter and Enterobacteriacea together accounted for 35% of the total average 16S rRNA ribotypes recovered from all specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In contrast, recent work in Costa Rican rolled-leaf beetles (Cephaloleia spp.) shows diet breadth is linked to microbiome diversity and community structure [21]. Previous research also indicates the composition of aphid microbial communities are structured by host plant [11,15,16,20,22,24,43,44] and heritable bacterial symbionts are involved in expanding diet breadth [23,25].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, recent work in Costa Rican rolled-leaf beetles (Cephaloleia spp.) shows diet breadth is linked to microbiome diversity and community structure [21]. Previous research also indicates the composition of aphid microbial communities are structured by host plant [11,15,16,20,22,24,43,44] and heritable bacterial symbionts are involved in expanding diet breadth [23,25].…”
Section: Discussionmentioning
confidence: 97%
“…Further research investigating the generalist-specialist gradient using herbivores that feed across multiple plant families is needed to clarify the extent to which diet breadth shapes microbial communities (e.g. [21]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…87 suggested they aided in the digestion of plant nectar consumed by Aedes albopictus mosquitoes. It was also suggested that they may help detoxify defensive plant compounds for tropical herbivorous beetles 88 . They also secrete antiparasitic compounds in the guts of several insects 89 .…”
Section: Discussionmentioning
confidence: 99%
“…Insect microbiomes consist of varying combinations of heritable symbionts and exible pools of environmentally acquired microbes, but how host plant range shapes the taxonomic and functional diversity of these communities is [21][22][23]relatively unexplored [5,[24][25][26]. Variation in host plant range can in uence the assembly of microbial communities and dynamics of symbiotic partnerships.…”
Section: Introductionmentioning
confidence: 99%